Transition metal-free oxidative and deoxygenative C–H/C–Li cross-couplings of 2H-imidazole 1-oxides with carboranyl lithium as an efficient synthetic approach to azaheterocyclic carboranes - Smyshliaeva, Lidia A.; Varaksin, Mikhail V.; Slepukhin, Pavel A.; Chupakhin, Oleg N.; Charushin, Valery N. (Beilstein Journal of Organic Chemistry, 2018)
The direct C–H functionalization methodology has first been applied to perform transition metal-free C–H/C–Li cross-couplings of 2H-imidazole 1-oxides with carboranyllithium. This atom- and step-economical approach, based on one-pot reactions of nucleophilic substitution of hydrogen (SNH) in non-aromatic azaheterocycles, affords novel imidazolyl-modified carboranes of two types (N-oxides and their deoxygenative analogues), which are particularly of interest in the design of advanced materials.
Keywords: carboranes; C–H functionalization; C–H/C–Li cross-coupling; 2H-imidazole 1-oxide; nucleophilic substitution of hydrogen (SNH)

Carboranes - Grimes, R. N. (Elsevier Inc., 2016)

(untitled) - Calabrese, G.; Daou, A.; Rova, A.; Tseligka, E.; Vizirianakis, S. I.; Fatouros, G. D.; Tsibouklis, J. (Med. Chem. Commun., 2017)

(untitled) - Núñez, R.; Tarrés, M.; Ferrer-Ugalde, A.; de Biani, F. F.; Teixidor, F. (Chem. Rev., 2016)

(untitled) - Paxton, R. J.; Beatty, B. G.; Hawthorne, M. F.; Varadarajan, A.; Williams, L. E.; Curtis, F. L.; Knobler, C. B.; Beatty, J. D.; Shively, J. E. (Proc. Natl. Acad. Sci. U. S. A., 1991)

(untitled) - Hawthorne, M. F.; Maderna, A. (Chem. Rev., 1999)

(untitled) - Genady, A. R.; Tan, J.; El-Zaria, M. E.; Zlitni, A.; Janzen, N.; Valliant, J. F. (J. Organomet. Chem., 2015)

(untitled) - Gómez-Vallejo, V.; Vázquez, N.; Gona, K. B.; Puigivila, M.; González, M.; Sebastián, E. S.; Martin, A.; Llop, J. (J. Labelled Compd. Radiopharm., 2014)

(untitled) - Calabrese, G.; Daou, A.; Barbu, E.; Tsibouklis, J. (Drug Discovery Today, 2018)

(untitled) - Khalil, A.; Ishita, K.; Ali, T.; Tjarks, W. (Future Med. Chem., 2013)

(untitled) - da Silva, A. F. F.; Seixas, R. S. G. R.; Silva, A. M. S.; Coimbra, J.; Fernandes, A. C.; Santos, J. P.; Matos, A.; Rino, J.; Santos, I.; Marques, F. (Org. Biomol. Chem., 2014)

(untitled) - Lee, C.-H.; Jin, G. F.; Yoon, J. H.; Jung, Y. J.; Lee, J.-D.; Cho, S.; Nakamura, H.; Kang, S. O. (Tetrahedron Lett., 2008)

(untitled) - Genady, A. R. (Eur. J. Med. Chem., 2009)

(untitled) - Issa, F.; Kassiou, M.; Rendina, L. M. (Chem. Rev., 2011)

(untitled) - Couto, M.; García, M. F.; Alamón, C.; Cabrera, M.; Cabral, P.; Merlino, A.; Teixidor, F.; Cerecetto, H.; Viñas, C. (Chem. – Eur. J., 2018)

(untitled) - Neumann, W.; Xu, S.; Sárosi, M. B.; Scholz, M. S.; Crews, B. C.; Ghebreselasie, K.; Banerjee, S.; Marnett, L. J.; Hey-Hawkins, E. (ChemMedChem, 2016)

(untitled) - Fujii, S.; Ohta, K.; Goto, T.; Kagechika, H.; Endo, Y. (Bioorg. Med. Chem., 2009)

(untitled) - Ohta, K.; Goto, T.; Fujii, S.; Suzuki, T.; Ohta, S.; Endo, Y. (Bioorg. Med. Chem., 2008)

(untitled) - Selg, C.; Neumann, W.; Lönnecke, P.; Hey-Hawkins, E.; Zeitler, K. (Chem. – Eur. J., 2017)

(untitled) - Tsang, M. Y.; Viñas, C.; Teixidor, F.; Planas, J. G.; Conde, N.; SanMartin, R.; Herrero, M. T.; Domínguez, E.; Lledós, A.; Vidossich, P.; Choquesillo-Lazarte, D. (Inorg. Chem., 2014)

(untitled) - Estrada, J.; Lavallo, V. (Angew. Chem., Int. Ed., 2017)

(untitled) - Wang, X.; Jin, G.-X. (Chem. – Eur. J., 2005)

(untitled) - Axtell, J. C.; Kirlikovali, K. O.; Djurovich, P. I.; Jung, D.; Nguyen, V. T.; Munekiyo, B.; Royappa, A. T.; Rheingold, A. L.; Spokoyny, A. M. (J. Am. Chem. Soc., 2016)

(untitled) - Li, X.; Tong, X.; Yan, H.; Lu, C.; Zhao, Q.; Huang, W. (Chem. – Eur. J., 2016)

(untitled) - Nghia, N. V.; Oh, J.; Jung, J.; Lee, M. H. (Organometallics, 2017)

(untitled) - Bae, H. J.; Chung, J.; Kim, H.; Park, J.; Lee, K. M.; Koh, T.-W.; Lee, Y. S.; Yoo, S.; Do, Y.; Lee, M. H. (Inorg. Chem., 2014)

(untitled) - Berksun, E.; Nar, I.; Atsay, A.; Özçeşmeci, I.; Gelir, A.; Hamuryudan, E. (Inorg. Chem. Front., 2018)

(untitled) - Neirynck, P.; Schimer, J.; Jonkheijm, P.; Milroy, L.-G.; Cigler, P.; Brunsveld, L. (J. Mater. Chem. B, 2015)

(untitled) - Zhao, J.; Jiang, S.; Chen, Y.; Chen, X.; Yang, Q.; Yin, C. (Polyhedron, 2018)

(untitled) - Mourier, N. S.; Eleuteri, A.; Hurwitz, S. J.; Tharnish, P. M.; Schinazi, R. F. (Bioorg. Med. Chem., 1999)

(untitled) - Tanui, H. K.; Hao, E.; Ihachi, M. I.; Fronczek, F. R.; Smith, K. M.; Vicente, G. H. (J. Porphyrins Phthalocyanines, 2011)

(untitled) - Zhao, D.; Zhang, J.; Xie, Z. (J. Am. Chem. Soc., 2015)

(untitled) - Zhao, D.; Zhang, J.; Xie, Z. (J. Am. Chem. Soc., 2015)

(untitled) - Zhao, D.; Xie, Z. (Coord. Chem. Rev., 2016)

(untitled) - Alekseyeva, E. S.; Batsanov, A. S.; Boyd, L. A.; Fox, M. A.; Hibbert, T. G.; Howard, J. A. K.; MacBride, J. A. H.; Mackinnon, A.; Wade, K. (Dalton Trans., 2003)

(untitled) - Weber, L.; Kahlert, J.; Brockhinke, R.; Böhling, L.; Brockhinke, A.; Stammler, H.-G.; Neumann, B.; Harder, R. A.; Fox, M. A. (Chem. – Eur. J., 2012)

(untitled) - Clarke, P. A.; Zaytzev, A. V.; Whitwood, A. C. (Tetrahedron Lett., 2007)

(untitled) - Clarke, P. A.; Ermanis, K. (Curr. Org. Chem., 2013)

(untitled) - Elinson, M. N.; Ryzhkov, F. V.; Korolev, V. A.; Egorov, M. P. (Heterocycl. Commun., 2016)

C–H Bond Activation in Organic Synthesis - Li, J. J. (CRC Press, 2015)

C–H Bond Activation and Catalytic Functionalization I and II - Dixneuf, P. H.; Doucet, H. (Springer, 2016)

(untitled) - Murakami, K.; Yamada, S.; Kaneda, T.; Itami, K. (Chem. Rev., 2017)

(untitled) - Shang, R.; Ilies, L.; Nakamura, E. (Chem. Rev., 2017)

Modern Nucleophilic Aromatic Substitution - Terrier, F. (Wiley-VCH, 2013)

Topics in Heterocyclic Chemistry - Charushin, V.; Chupakhin, O. (Metal Free C-H Functionalization of Aromatics Nucleophilic Displacement of Hydrogen, 2014)

(untitled) - Chupakhin, O. N.; Charushin, V. N. (Tetrahedron Lett., 2016)

(untitled) - Błaziak, K.; Danikiewicz, W.; Makosza, M. (J. Am. Chem. Soc., 2016)

(untitled) - Kiriazis, A.; Aumüller, I. B.; Arnaudova, R.; Brito, V.; Rüffer, T.; Lang, H.; Silvestre, S. M.; Koskinen, P. J.; Yli-Kauhaluoma, J. (Org. Lett., 2017)

(untitled) - Chupakhin, O. N.; Charushin, V. N. (Pure Appl. Chem., 2017)

Green Chemistry and Catalysis - Sheldon, R. A.; Arends, I.; Hanefeld, U. (John Wiley & Sons, 2007)

(untitled) - Mulvihill, M. J.; Beach, E. S.; Zimmerman, J. B.; Anastas, P. T. (Annu. Rev. Environ. Resour., 2011)

Green Chemistry. An Introductory Text - Lancaster, M. (RSC Publishing, 2010)

(untitled) - Anastas, P.; Eghbali, N. (Chem. Soc. Rev., 2010)

SpringerBriefs in Molecular Science - Dicks, A. P.; Hent, A. (Green Chemistry Metrics)

(untitled) - Prokhorov, A. M.; Hofbeck, T.; Czerwieniec, R.; Suleymanova, A. F.; Kozhevnikov, D. N.; Yersin, H. (J. Am. Chem. Soc., 2014)

(untitled) - Prokhorov, A. M.; Slepukhin, P. A.; Rusinov, V. L.; Kalinin, V. N.; Kozhevnikov, D. N. (Chem. Commun., 2011)

(untitled) - Galliamova, L. A.; Varaksin, M. V.; Chupakhin, O. N.; Slepukhin, P. A.; Charushin, V. N. (Organometallics, 2015)

(untitled) - Varaksin, M.; Moseev, T.; Chupakhin, O.; Charushin, V.; Trofimov, B. (Org. Biomol. Chem., 2017)

(untitled) - Zubenko, D.; Kirilyuk, I.; Roschchupkina, G.; Zhurko, I.; Reznikov, V.; Marque, S. R. A.; Bagryanskaya, E. (Helv. Chim. Acta, 2006)

(untitled) - Edeleva, M. V.; Parkhomenko, D. A.; Morozov, D. A.; Dobrynin, S. A.; Trofimov, D. G.; Kanagatov, B.; Kirilyuk, I. A.; Bagryanskaya, E. G. (J. Polym. Sci., Part A: Polym. Chem., 2014)

(untitled) - Varaksin, M. V.; Utepova, I. A.; Chupakhin, O. N.; Charushin, V. N. (J. Org. Chem., 2012)

(untitled) - You, Y.; Kim, H. S.; Bae, I. H.; Lee, S. G.; Jee, M. H.; Keum, G.; Jang, S. K.; Kim, B. M. (Eur. J. Med. Chem., 2017)

(untitled) - Tsay, S. C.; Lin, S. Y.; Huang, W. C.; Hsu, M. H.; Hwang, K. C.; Lin, C. C.; Horng, J. C.; Chen, I. C.; Hwu, J. R.; Shieh, F. K. (Molecules, 2016)

(untitled) - Abdelazeem, A. H.; El-Saadi, M. T.; Safi El-Din, A. G.; Omar, H. A.; El-Moghazy, S. M. (Bioorg. Med. Chem., 2017)

(untitled) - Hu, Y.; Shen, Y.; Wu, X.; Tu, X.; Wang, G.-X. (Eur. J. Med. Chem., 2018)

(untitled) - Ali, I.; Lone, M. N.; Aboul-Enein, H. Y. (Med. Chem. Commun., 2017)

(untitled) - Popescu, A.-R.; Musteti, A. D.; Ferrer-Ugalde, A.; Viñas, C.; Núñez, R.; Teixidor, F. (Chem. – Eur. J., 2012)